Planar Waveguide from PPV Derivatives - F. Fitrilawati; M.O. Tjia; H. Eichner; C. Bubeck (Institute for Research and Community Services (LPPM) ITB, 2001)
Abstract. We report in this paper the result of thin film fabrication of MEH-PPV and MEH-PPB having good optical transparency and low surface roughness suitable for planar waveguide application. The linear optical properties of the polymers were characterized using reflectometry and prism coupling, while the non-linear optical property was measured by means of optical third harmonic generation (THG). The waveguide attenuation of the polymer films was determined by employing prism coupling set-up equipped with a photodiode array detector. The MEH-PPV waveguide film was shown to have a very low attenuation of 0.5 dB cm-1 at 1064 nm yielding an unprecedentedly high figure of merits of 11 at 1 GW/cm2. Pandu Gelombang Planar dari Turunan PPVSari. Dalam tulisan ini dilaporkan fabrikasi film tipis polimer MEH-PPV dan MEH-PPB yang mempunyai transparansi optik tinggi dan permukaan yang halus sehingga cocok untuk aplikasi pandu gelombang planar. Sifat optic linier dari polimer yang bersangkutan diukur dengan teknik reflektometri dan kopling prisma dan sifat optic nonlinier diukur dengan metoda third harmonic generation (THG). Selanjutnya, atenuasi pandu gelombang dari film polimer yang bersangkutan diukur dengan konfigurasi kopling prisma dan detector diode arrat. Film pandu gelombang yang dihasilkan dalam eksperimen ini memiliki atenuasi rendah sebesar 0.5 dB cm-1 pada panjang gelombang 1064 nm dan menghasilkan